An efficient implementation of a runtime for constraint-logic object-oriented programming - Hendrik Winkelmann (University of Münster, European Research Center for Information Systems (ERCIS), 2024)
In this technical report the symbolic execution engine 'Mulib' will be outlined in its architecture, main algorithms, and design decisions. Mulib employs a rather new approach of program transformation (see Section 2) and thus, technical details on the implementation of such a system are thought to be insightful. Mulib first and foremost implements the runtime semantics of the Constraint-Logic Object-Oriented Programming (CLOOP) language Muli. Muli employs symbolic execution as a technique to, e.g., solve constraint-satisfaction problems and generate test cases.
Keywords: 650